2007
DOI: 10.1007/s10529-006-9289-y
|View full text |Cite
|
Sign up to set email alerts
|

Pt-based electro-catalytic materials derived from biosorption processes and their exploitation in fuel cell technology

Abstract: Yeast-based biomass, immobilised in polyvinyl alcohol (PVA) cryogels, was used as a biosorbant material for the recovery of platinum (PtCl (6) (2-) ) from aqueous solutions. The resulting biomass-Pt matrices were then employed directly as an electro-catalytic anode in a fuel cell configuration to generate electrical energy from renewable sources such as glucose and ethanol. We suggest an integrated strategy incorporating the derivation of a high-value product from a bioremediative process with a view towards p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Mikheenko and P. Yong, unpublished). A similar strategy was also suggested using waste yeast from ethanol production for the manufacture of fuelcell Pt(0) (Dimitriadis et al 2007). These two examples clearly show the feasibility of sustainable integrated energy generating systems made from wastes, while the use of precious metal scrap as a resource (Mabbett et al 2006) indicates that as vehicles switch from fossil-fuels to hydrogen power the spent automotive catalysts could be usefully diverted to economic fuel cell production.…”
Section: Tests Of Bio-pt and Pd Catalysts In A Pem Fuel Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Mikheenko and P. Yong, unpublished). A similar strategy was also suggested using waste yeast from ethanol production for the manufacture of fuelcell Pt(0) (Dimitriadis et al 2007). These two examples clearly show the feasibility of sustainable integrated energy generating systems made from wastes, while the use of precious metal scrap as a resource (Mabbett et al 2006) indicates that as vehicles switch from fossil-fuels to hydrogen power the spent automotive catalysts could be usefully diverted to economic fuel cell production.…”
Section: Tests Of Bio-pt and Pd Catalysts In A Pem Fuel Cellmentioning
confidence: 99%
“…Other studies have shown that Pd/Pt nanoparticles biomanufactured from real processing wastewater have high catalytic activity (Mabbett et al 2006). Bacterial-supported biogenic nanoparticles have not been considered for use in fuel cell applications although a parallel study has suggested the use of biosorbed platinum on yeast biomass followed by electroreduction to Pt(0) for this application (Dimitriadis et al 2007). The objective of this study was to produce electrocatalysts using Pt and Pd biomineralised from metal solutions and prove the capability of the bioelectrodes to generate electricity in a PEM fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-derived PM nanoparticles are alternative fuel cell quality catalysts (Dimitriadis et al 2007;Yong et al 2007), the dual biosynthesis and nanoparticle-supporting functions overcoming the agglomeration problems that can beset conventional, non-biological methods of nanoparticle catalyst manufacture (see Creamer et al 2007). Catalytically active Pd(0) nanoparticles were manufactured by Desulfovibrio desulfuricans and also by E. coli (Deplanche, 2008;Orozco et al 2010), prompting the possibility to utilise waste E. coli biomass from biohydrogen production as the precursor to a fuel cell catalyst (Orozco et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some chemical compounds of yeast cells can act as ion exchangers with rapid, reversible binding of cations whereas for metal removal and recovery from aqueous solutions, dead fungal biomass seems to offer several advantages; such biomass is often a by-product of industrial processes and may be obtained inexpensively, biosorption kinetics are not affected by metal toxicity since there is no metabolic activity, the biomass does not require nutrient supply and is not affected by the recovery of surface-bound metals (Volesky and Holan, 1995;Vieira and Volesky, 2000). Some studies (Volesky et al, 1994) indicate that the most common yeast biomass (Saccharomyces cerevisiae) is an effective biosorbent material and it has been used for Pt(IV) recovery into a proton-exchange membrane fuel cell (PEMFC) to generate electricity following reduction of sorbed Pt(IV) (Dimitriadis et al, 2007). Another industrially important organism, the fungus Penicillium chrysogenum, has been shown to extract Au(III) from cyanide solution through anionic gold cyanide species adsorption onto N -, P -or Ocontaining functional groups on the biomass.…”
Section: Case Study 1: Biorecovery Of Pgms From Spent Car Catalyst Anmentioning
confidence: 99%